Enhancement of the motility during the liquid storage of ram semen by argan oil - Allai L.; El Amiri B.; Druart X.; Fatet A.; Nasser B. (Technology creation and transfer in small ruminants: roles of research, development services and farmer associations, 2014)
The aim of this study was to evaluate the motility of fresh ram semen after addition of different concentrations of argan oil. Semen was collected from five adult fertile Boujaâd rams (3-4 years of age) with artificial vagina. Ejaculates were diluted to a final concentration of 0.8 x 109 sperm/ml with TRIS-egg yolk diluent supplemented with argan oil at different concentrations: 0 (control), 1, 5, and 10% v/v. Semen was then stored at 15°C and sperm motility was evaluated at 0, 8, 24, 48 and 72 h post dilution with microscope (40 X magnification). Semen diluted and stored in the TRIS-egg yolk diluent supplemented with 1% of argan oil had higher sperm motility up to 3 days after collection as compared to the other concentrations used in this experiment. In conclusion, our results show that argan oil, which is rich in antioxidants, may have a protective effect allowing widening the duration of fresh ram semen conservation in Boujaâd breed.
8. Seminar of the FAO-CIHEAM Sub-Network on Production Systems, 2013/06/11-13, Tangier (Morocco)